Worhsipping Nandi with Shiva during Maha Shivaratri - Mumbai Archive Project Team (Jio Institute, 2024)
During Maha Shivaratri, Nandi is worshipped along with Shiva. The Nandi statue is bathed with milk, water, bael leaves, and other sacred items in a ritual similar to the abhishekam performed for the lingam.